Exploration of the key functional proteins from an efficient cellulolytic microbial consortium using dilution-to-extinction approach - Zhang, Qinghua; Li, Hanguang; Zhu, Xiangdong; Lai, Fenju; Zhai, Zhijun; Wang, Yuanxiu (Journal of environmental sciences (China), 2016)
In the present study, the cellulose binding proteins（CBPs） secreted by a putative cellulolytic microbial consortium were isolated and purified by affinity digestion. The purified CBPs were subsequently separated by sodium dodecyl sulfate–polyacrylamide gel electrophoresis（SDS-PAGE）. Using mass spectrometric analyses, eight CBPs were identified and annotated to be similar to known proteins secreted by Clostridium clariflavum DSM 19732 and Paenibacillus sp. W-61. In addition, in combination with dilution-to-extinction approach and zymogram analysis technique, CBPs 6（97 k Da） and 12（52 k Da） were confirmed to be the key functional proteins that influence cellulolytic activities. Moreover, structural domain analyses and enzymatic activity detection indicated that CBPs 6 and 12 contained glycoside hydrolase families（GH） 9 and 48 catalytic modules, which both revealed endoglucandase and xylanase activities. It was suggested that the coexistence of GH9 and GH48 catalytic domains present in these two proteins could synergistically promote the efficient degradation of cellulose.